A Case Study To Examine Undergraduate Students’ Intention To Use Internet Of Things (IoT) ServicesIin The Smart Classroom - Ameer Alhasan; Mahmood H. Hussein; Lukman Audah; Ammar Al-Sharaa; Ishaq Ibrahim; Moamin A. Mahmoud (Springer Science and Business Media LLC, 2024)
Indexed by WOS/Scopus/ERA